A novel event-triggered strategy for networked switched control systems. Issue 1 (January 2021) - Gao, Hui; Shi, Kaibo; Zhang, Hongbin
Abstract: This paper investigates the problem of event-triggered finite-time control for networked switched control systems with extended dissipative performance. Different from previous event-triggered results of switched systems, we propose a novel event-triggered method that allows more than once system switching over an event-triggered interval. By using a new Lyapunov function method, we discussed the finite-time extended dissipative analysis of the closed-loop networked switched systems. The controller gains and event-triggered parameters are obtained by solving some LMIs. Finally, numerical examples are given to illustrate the effectiveness of the proposed method.